How Unique Cultural Concept Translation is Made Possible - Sugeng Hariyanto (Pascasarjana UM, 2017)
Abstract: The plethora of experience in one culture is stored in concepts which are further manifested in the lexicon, grammar and metaphors of the language. Some concepts are congruent across languages, while some are not. Theoretically, some linguists maintain that translation is impossible on the ground of linguistic relativity hypothesis. However, in practice translation is always done again and again, and this proves that translation of expressions referring to these concepts is doable. Considering the discussion of the elements of conceptual systems presented here, the writer proposes three ways of translating expressions to convey concepts: (a) compensating the element of a concept with another element of the same concept, (b) separating concepts from words or expression, and (c) bringing the concept and expressions into the target language using loan word/expression with or without any notes, or bringing the concept into the target language using descriptions. To help select an appropriate way of translating in a particular case, translators should consider the translation purpose. As the discussion unfolds, examples are presented to illustrate the situation.Key Words: linguistic relativity, concept, conceptual system, grammaticization, lexicalization, metaphor, compensationAbstrak: Kebanyakan pengalaman dalam satu budaya tersimpan dalam konsep yang terwujud dalam leksikon, tata bahasa, dan metafora bahasa. Beberapa konsep kongruen di seluruh bahasa, sementara beberapa lainnya tidak. Secara teoritis, beberapa ahli bahasa berpendapat bahwa terjemahan itu tidak mungkin berdasarkan hipotesis relativitas linguistik. Namun, dalam praktiknya terjemahan selalu dilakukan berulang-ulang, dan ini membuktikan bahwa terjemahan ungkapan yang mengacu pada konsep ini dapat dilakukan. Mengingat pembahasan tentang unsur-unsur sistem konseptual yang dipaparkan di sini, diajukan tiga cara untuk menerjemahkan ekspresi untuk menyampaikan konsep: (a) mengkompensasi unsur konsep dengan elemen lain dari konsep yang sama, (b) memisahkan konsep dari kata atau ungkapan, dan (c) membawa konsep dan ungkapan ke dalam bahasa target menggunakan kata/ekspresi pinjaman dengan atau tanpa catatan, atau membawa konsep ke bahasa target menggunakan deskripsi. Untuk membantu memilih cara menerjemahkan yang tepat dalam kasus tertentu, penerjemah mempertimbangkan tujuan penerjemahan. Seiring diskusi dipaparkan, disajikan contoh untuk menggambarkan situasi.Kata kunci: relativitas linguistik, konsep, sistem konseptual, gramatisasi, leksikalisasi, metafor, kompensasi